Indonesian Food Diplomacy and Diaspora Soft Power in Madinah - Kurniawan Arif Maspul; Hasbi Yusron (ROE: Research of Economics and Business, 2026)
This study posits that the Indonesian diaspora in Madinah particularly its students is pioneering a transformative model of 'everyday diplomacy' that is fundamentally reshaping Indonesia’s influence within the Muslim world. Moving beyond state-centric gastrodiplomacy, this research illuminates how grassroots culinary practices in the sacred city from campus food festivals to local eateries near the Prophet’s Mosque serve as a potent, decentralised soft-power network. In the unique socio-religious milieu of Madinah, where millions of pilgrims converge, each shared plate of rendang or soto operates as a compact cultural performance, building affective bonds that formal diplomacy cannot easily replicate. This paper argues that this bottom-up, diaspora-led engagement is not merely cultural exchange but a strategic foreign policy asset, directly fueling national economic objectives like the 'Indonesia Spice Up the World' initiative. These commonplace acts lead to tangible outcomes: greater spice exports, better educational linkages, and increased tourism appeal. This study concludes that Indonesia’s success in Madinah offers a blueprint for how emerging Global South powers can leverage non-state actors and cultural affinity to build sustainable, resilient influence in the 21st century, one plate at a time.